2021
DOI: 10.1126/sciadv.abg5381
|View full text |Cite
|
Sign up to set email alerts
|

Helical springs as a color indicator for determining chirality and enantiomeric excess

Abstract: Chirality plays a key role in the physiological system, because molecular functionalities may drastically alter due to a change in chirality. We report herein a unique color indicator with a static helicity memory, which exhibits visible color changes in response to the chirality of chiral amines. A difference of less than 2% in the enantiomeric excess (ee) values causes a change in the absorption that is visible to the naked eyes. This was further quantified by digital photography by converting to RGB values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…It is commonly applied to assess cis‐ or trans‐ content in PPAs and PDPAs [51, 99, 100] . Catalysts based on tungsten (W) are known to provide trans ‐rich PDPAs as shown in many examples in the literature, [99, 100] albeit Maeda recently demonstrated that in the case of symmetric PDPAs, polyene backbones with a predominant cis‐ content of double bonds are also obtained [79, 80] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly applied to assess cis‐ or trans‐ content in PPAs and PDPAs [51, 99, 100] . Catalysts based on tungsten (W) are known to provide trans ‐rich PDPAs as shown in many examples in the literature, [99, 100] albeit Maeda recently demonstrated that in the case of symmetric PDPAs, polyene backbones with a predominant cis‐ content of double bonds are also obtained [79, 80] …”
Section: Resultsmentioning
confidence: 99%
“…Another interesting family of helical polymers are the poly(diphenylacetylene)s (PDPAs) [71–93] that resemble PPAs in the main chain, which in both cases is made up of conjugated double bonds. However, the presence of a phenyl group on each carbon of the double bond in PDPAs makes the properties of both materials very different.…”
Section: Introductionmentioning
confidence: 99%
“…[51,99,100] Catalysts based on tungsten (W) are known to provide trans-rich PDPAs as shown in many examples in the literature, [99,100] albeit Maeda recently demonstrated that in the case of symmetric PDPAs, polyene backbones with a predominant cis-content of double bonds are also obtained. [79,80] Herein, we will study the stereoregularity of poly-1 and poly-(S)-2 by comparison of their Raman spectra with those obtained for PPAs with well-known secondary structure. Therefore, as model compounds we chose poly-(3-6) (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, PDPAs show better chemical, thermal and photochemical stability compared to PPAs. [72][73][74][75][76][77][78][79][80][81][82][83][84][85] Moreover, PDPAs exhibit another interesting property that PPAs do not have, i.e. photoluminescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation